2006
DOI: 10.1177/1087057106289403
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition Profiling of Human Carbonic Anhydrase II by High-Throughput Screening of Structurally Diverse, Biologically Active Compounds

Abstract: Human carbonic anhydrase II (CA II), a zinc metalloenzyme, was screened against 960 structurally diverse, biologically active small molecules. The assay monitored CA II esterase activity against the substrate 4-nitrophenyl acetate in a format allowing high-throughput screening. The assay proved to be robust and reproducible with a hit rate of approximately 2%. Potential hits were further characterized by determining their IC(50) and K(d) values and tested for nonspecific, promiscuous inhibition. Three known su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
49
0
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 65 publications
(54 citation statements)
references
References 38 publications
4
49
0
1
Order By: Relevance
“…The CA II expression plasmid, pACA, was a generous gift from Dr. Carol Fierke, University of Michigan. Bacterial expression and purification of CA II on a SP Sepharose Fast Flow (Amersham Biosciences/GE Healthcare, Piscataway, NJ) cation exchange column were performed as described previously (1). SDS-PAGE analysis indicated that the CA II had greater than 95% purity.…”
Section: Methodsmentioning
confidence: 99%
See 4 more Smart Citations
“…The CA II expression plasmid, pACA, was a generous gift from Dr. Carol Fierke, University of Michigan. Bacterial expression and purification of CA II on a SP Sepharose Fast Flow (Amersham Biosciences/GE Healthcare, Piscataway, NJ) cation exchange column were performed as described previously (1). SDS-PAGE analysis indicated that the CA II had greater than 95% purity.…”
Section: Methodsmentioning
confidence: 99%
“…The upper limit of substrate concentration (0.5 mM) was within the typical range of 0.4 to 1.0 mM 4-NPA concentration used in CA activity assays (1,52,65) and is far in excess of the enzyme concentration (1 µM). The substrate concentration is well below experimental estimates of K M for this enzyme-substrate combination, which, because of the relatively low solubility of 4-NPA in aqueous solution, vary between 4 and 22 mM (52,81).…”
Section: Enzyme Kinetic Studiesmentioning
confidence: 99%
See 3 more Smart Citations